Peningkatan Kemampuan Berkomunikasi Dengan Peserta Didik Melalui Supervisi Klinis Bagi Guru SD Negeri 5 Surabaya Pada Semester I Tahun Ajaran 2016/2017 - Vera Vonette; Ian Indrata; Hasondrorogo Daya; Elisabet Kristanti; Arlawati Ginting (Jurnal Teologi dan Pelayanan Kerusso, 2018)
The ability of teachers to manage student interactions in learning activities relates to communication between students and other students, students with teachers and vice versa. The purpose of this study was to measure the improvement in the ability of Surabaya Elementary School 5 teachers to communicate with students after clinical supervision. This classroom action research was carried out by taking place at SD Negeri 5 Surabaya. The school's action research was conducted in the first semester of the 2016/2017 school year. The subject of this study was the teacher of SD Negeri 5 Surabaya, amounting to six teachers. The results of this study are the teacher's ability to communicate with students from cycle to cycle has increased, namely from prasiklus 33.86%, the first cycle of 66.08%, and the second cycle of 88.30%, so that the increase during the action is 54, 44%. Increases occur in all aspects. The increase in teachers' abilities was due to clinical supervision activities based on objective assessments that were delivered transparently to teachers, besides the implementation of supervision with a small number of teachers tended to facilitate communication between researchers, principals and teachers. The existence of such supervision increases the teacher's awareness of the importance of the ability to communicate with students, and raises the awareness of teachers that this ability is one aspect of teacher performance assessment.